2015
DOI: 10.4238/2015.may.18.16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high-concentrate diet on amino acid transporter expression and milk quality in Holstein dairy cows

Abstract: ABSTRACT. In order to evaluate the effect of high-concentrate diet supplementation on milk protein content, six Holstein dairy cows were assigned into high-concentrate diet (HC) or low-concentrate diet (LC) groups (N = 3/group) for 50 days. With regard to milk protein, HC feeding significantly reduced the percentage of milk protein (P < 0.01), and milk protein yield also reduced. The milk somatic cell count numbers and N-acetyl-D-glucosaminidase activity was significantly higher (P < 0.01) in the HC group than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
1
1
Order By: Relevance
“…Figure 2A shows that the average SCC was higher in HC-fed cattle, achieving 166,733 cells/mL, but did not achieve the threshold of 205,000 cells/mL (Rodrigues et al, 2009). These results were similar to those of our previous research, which showed that feeding a HC diet to cattle depressed milk quality (Xie et al, 2015b). However, in the present study, the SCC content and NAGase activity were higher than observed in our previous study (Xie et al, 2015b), because here we extended the experimental period.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Figure 2A shows that the average SCC was higher in HC-fed cattle, achieving 166,733 cells/mL, but did not achieve the threshold of 205,000 cells/mL (Rodrigues et al, 2009). These results were similar to those of our previous research, which showed that feeding a HC diet to cattle depressed milk quality (Xie et al, 2015b). However, in the present study, the SCC content and NAGase activity were higher than observed in our previous study (Xie et al, 2015b), because here we extended the experimental period.…”
Section: Discussionsupporting
confidence: 82%
“…These results were similar to those of our previous research, which showed that feeding a HC diet to cattle depressed milk quality (Xie et al, 2015b). However, in the present study, the SCC content and NAGase activity were higher than observed in our previous study (Xie et al, 2015b), because here we extended the experimental period. We therefore hypothesized that cattle mammary epithelial cells may suffer from sub-clinical mastitis when animals are fed a HC diet over a relatively long experimental period.…”
Section: Discussioncontrasting
confidence: 37%
“…This result suggests that goats with SARA experience stress ( Dong et al., 2013 ; Jia et al., 2014 ). Furthermore, many studies have found that a high concentrate diet causes liver metabolic abnormalities, including glucose metabolism, lipid metabolism, and protein metabolism ( Dong et al., 2013 ; Xie et al., 2015 ). In addition, a high concentrate diet induces oxidative stress in the liver.…”
Section: Discussionmentioning
confidence: 99%